Effect of quercetin on the amiloride–bovine serum albumin interaction using spectroscopic methods, molecular docking and chemometric approaches. (19th August 2020) - Shinde, Mandakini; Kale, Kishor; Kumar, Keshav; Ottoor, Divya
Abstract: The effect of quercetin flavonoid (QUE), on the binding interaction of antihypertensive drug, amiloride (AMI) with bovine serum albumin (BSA) was investigated in this study. Spectroscopic methods such as steady‐state, synchronous, three‐dimensional fluorescence, and circular dichroism spectroscopy were employed to study the interaction. Fluorescence data were analyzed using the Stern–Volmer equation and a static quenching process was found to be involved in the formation of AMI–BSA and QUE–BSA complexes and were in good agreement with the thermodynamic study. The thermodynamic parameters illustrated that the process is spontaneous and enthalpy driven. Hydrophobicity is acting as the primary force in the binding interaction. Fluorescence spectral data were resolved using a multivariate curve resolution‐alternating least squares method (MCR–ALS). Site marker and molecular docking studies confirmed the binding site of AMI on BSA, i.e. site II. The binding distance between amino acid of BSA and AMI was calculated and found to be 2.18 nm which indicated that energy transfer has occurred from an amino acid of BSA to AMI. The binding affinity of AMI to BSA was found to be reduced in the presence of QUE, which may lead to the poor distribution of AMI at the desired site. Abstract : Present work deals with the effect of quercetin on amiloride ‐ BSA interaction by fluorescence spectroscopy. It was found that binding constant of AMI to BSA reduced in the presence of QUE. Quenching mechanism was confirmed by temperature dependent fluorescence experiments and molecular docking. Conformational changes occurred in BSA on interaction with AMI was observed by CD, synchronous fluorescence and 3D fluorescence. Results provide information related to the antagonism effect of AMI and QUE interaction with BSA when they coexist.